Temperature and Humidity Stable Alkali/Alkaline‐Earth Metal Carbonates as Electron Heterocontacts for Silicon Photovoltaics. Issue 22 (28th May 2018) - Wan, Yimao; Bullock, James; Hettick, Mark; Xu, Zhaoran; Samundsett, Chris; Yan, Di; Peng, Jun; Ye, Jichun; Javey, Ali; Cuevas, Andres
Abstract: Nanometer scale interfacial layers between the metal cathode and the n‐type semiconductor play a critical role in enhancing the transport of charge carriers in and out of optoelectronic devices. Here, a range of nanoscale alkali and alkaline earth metal carbonates (i.e., potassium, rubidium, caesium, calcium, strontium, and barium) are shown to function effectively as electron heterocontacts to lightly doped n‐type crystalline silicon (c‐Si), which is particularly challenging to contact with common metals. These carbonate interlayers are shown to enhance the performance of n‐type c‐Si proof‐of‐concept solar cells up to a power conversion efficiency of ≈19%. Furthermore, these devices are thermally stable up to 350 °C and both the caesium and barium carbonates pass a standard 1000 h damp heat test, with >95% of their initial performance maintained. The temperature and humidity stable electron heterocontacts based on alkali and alkaline earth metal carbonates show a high potential for industrial feasibility and longevity for deployment in the field. Abstract : A series of temperature and humidity stable electron heterocontacts composed of a nanoscale of alkali/alkaline‐earth metal carbonates are developed for silicon photovoltaics, achieving a power conversion efficiency of ≈19%, being thermally stable up to 350 °C (for the six carbonates) and passing a standard 1000 h damp heat test (for the caesium and barium carbonates).